Analisis Kearifan Lokal di Taman Nasional Aketajawe Lolobata Kota Tidore Kepulauan Propinsi Maluku Utara (Studi Kasus Masyarakat Tobelo Dalam di Dusun Tayawi) - Wiwin Failysa Putri; Asar Said Mahbub; Muh. Dassir (Jurnal Hutan dan Masyarakat, 2019)
Local wisdom and local knowledge are very influential on the life of the Inner Tobelo Community in forest management in the Aketajawe Lolobata National Park in the Aketajawe block in Tayawi. This study aims to analyze the forms of local wisdom in forest management in the Tobelo Dalam community, as well as to examine the collaborative forms of the management of Aketajawe Lolobata National Park based on local wisdom.This study was conducted in February 2018 to May 2018 in the Aketajawe Lolobata National Park Aketajawe Block, Tayawi Hamlet, Koli Village, Oba Subdistrict, Tidore City Islands, North Maluku Province, Indonesia. This location was chosen as the location of the study because seeing the area of community life is still very dependent on the forest around it. The approach used in this study is qualitative descriptive and in-depeth interview with the aim of describing the forms of local wisdom in forest management in Aketajawe Lolobata National Park, especially in the Aketajawe Block in the Tayawi Village which includes land use, the system of labor, and utilization of non-timber forest products and directed also to illustrate how the collaboration model of Aketajawe National Park management is based on local wisdom, in this case the Stakeholders is the local Government and Local Community (Tobelo Dalam Community). The results showed that the existence of local wisdom used by the in Tobelo community in forest management based on rules and sanctions that had existed before had a very positive effect, so that the forest was maintained and sustainable. The collaboration or collaboration model between the government and the in Tobelo community is that the government always involves the Tobelo community in managing the national park aketajawe lolobata with the hope that the national park will be preserved, so far the types of collaboration or collaboration between the local government and the in Tobelo community management of the National Park, namely the government makes several in Tobelo Community as Guides for tourists coming to the National Park and also the government employs several Tobelo Dalam Communities to clean resort offices and National Park guest houses in the Tayawi resort, and making some people also as a security to maintain the office and guest house.